Three phragmalin-type limonoids orthoesters and the structure of odoratone isolated from the bark of Entandrophragma candollei (Meliaceae). (January 2021) - Happi, Gervais Mouthé; Mouthe Kemayou, Guy Paulin; Stammler, Hans-Georg; Neumann, Beate; Ismail, Mohamed; Kouam, Simeon Fogue; Wansi, Jean Duplex; Tchouankeu, Jean Claude; Frese, Marcel; Lenta, Bruno Ndjakou; Sewald, Norbert
Abstract: The phytochemical exploration of the Entandrophragma candollei stem bark extract led to the isolation and identification of twenty compounds including three undescribed phragmalin-class limonoids named encandollens C–E (1 –3 ), the undescribed protolimonoid 5 together with sixteen known compounds. The structures of all the isolated compounds were determined by interpretation of their spectroscopic and spectrometric data including HRMS, 1D and 2D NMR analyses. The assignment of the absolute and relative stereochemistry of the undescribed compounds was achieved using SC-XRD analyses as well as NOESY experiments. The previously reported structure of odoratone (5a ) was corrected as 23 R, 24 S-dihydroxy-22 S, 25-epoxytirucall-7-en-3-one (5 ) based on its NMR and SC-XRD data. Prieurianin (4 ) exhibited high cytotoxic activity on KB3-1 cell lines with an IC50 of 1.47 μM compared to the reference griseofulvin (IC50 = 17–21 μM). The results of the in silico docking of compound 4 supported and delivered further insights on its cytotoxicity. Graphical abstract: Image 1 Highlights: Three undescribed phragmalin-type limonoids encandollens C-E were obtained from Entandrophragma candollei. The structure of odoratone was corrected as 23 R, 24 S-dihydroxy-22 S, 25-epoxytirucall-7-en-3-one using its SC-XRD and NMR analyses. Three previously undescribed hemi-synthetic derivatives odoratonides I-III were obtained from acetonide preparation of odoratone. We reported the cytotoxicity of prieurianin and its molecular docking studies to enzymes human neutrophil collagenase MMP-8, tubulin and Human DNA topoisomerase I.